The auditory efferent system in mosquitoes - Loh, YuMin M.; Su, Matthew P.; Ellis, David A.; Andrés, Marta (Frontiers in Cell and Developmental Biology, 2023)
Whilst acoustic communication forms an integral component of the mating behavior of many insect species, it is particularly crucial for disease-transmitting mosquitoes; swarming males rely on hearing the faint sounds of flying females for courtship initiation. That males can hear females within the din of a swarm is testament to their fabulous auditory systems. Mosquito hearing is highly frequency-selective, remarkably sensitive and, most strikingly, supported by an elaborate system of auditory efferent neurons that modulate the auditory function - the only documented example amongst insects. Peripheral release of octopamine, serotonin and GABA appears to differentially modulate hearing across major disease-carrying mosquito species, with receptors from other neurotransmitter families also identified in their ears. Because mosquito mating relies on hearing the flight tones of mating partners, the auditory efferent system offers new potential targets for mosquito control. It also represents a unique insect model for studying auditory efferent networks. Here we review current knowledge of the mosquito auditory efferent system, briefly compare it with its counterparts in other species and highlight future research directions to unravel its contribution to mosquito auditory perception.